Waveform, memory and classical soft scalar theorems - Sarthak Duary; Pabitra Ray (Nuclear Physics B, 2025)
We examine a scattering process in which a set of particles come together, interact through a long-range massless scalar force like dilaton mediated and then disperse. Using worldline formalism, we compute the trajectories of the scattered particles and derive an infinite series of subleading terms in the late-time and early-time expansion of the scalar waveform. We study the scalar waveform, the scalar memory term and classical soft scalar theorems. We ignore gravitational interactions and discuss the challenges if we include them.